Peningkatan Karakter Disiplin Guru Melalui Diskusi Hasil Pemantauan Berkesinambungan di SD 2 Barongan UPT PP Kecamatan Jetis - Sarjiyati Sarjiyati (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
Improvement of Teacher Discipline Character Through Discussion of Continuous Monitoring Results in SD 2 Barongan, UPT PP Jetis District, 2017/2018. This school action research aims to improve the character of teacher discipline through discussion of the results of continuous monitoring in SD 2 Barongan. The background of this research is the lack of discipline character, the results of monitoring are not optimal and there are no discussion activities to discuss the results of monitoring. This type of research is the School Action Research (PTS). Subjects were 8 Barongan Elementary School teachers, totaling 8 teachers consisting of 2 male teachers and 6 female teachers. Data analysis techniques used in this study were qualitative descriptive and quantitative descriptions. This research was conducted in two cycles, and pre-action to determine the initial character of the discipline. Discussion activities of the harvesters in the first cycle of the first meeting are still in the sufficient category. The results of the discussion at the second meeting of the first cycle are in the good category, but the scores obtained are still low. The results of disciplinary observations at the first meeting are still in the sufficient category. At the second meeting of the first cycle the results of the character of discipline are already in the good category, with a score that is still low. Cycle II of the first meeting the results of the discussion were in the good category. At the second meeting the score increases with the score increasing. In the initial conditions, the average character discipline score was 28,625. In the first cycle the average score of discipline characters increased to 31.56 with a good category. Furthermore, in the second cycle of action, an increase with an average grade of 42.25 with a good category. Thus it can be concluded that by discussing the results of continuous use in schools can improve the character of teacher discipline in SD 2 Barongan.